Meningkatkan Pengenalan Masyarakat terhadap Jenis Bangun Ruang melalui Platonic Solid - Maslina Simanjuntak (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2017)
The background of this paper is the defecient of the society’s recognition of geometry in mathematics. The purpose of this paper is to introduce closer the society to the uniqueness of geometry in mathematics, so that the community’s knowledge about the variety of geometry in mathematic will increase and grow broader. This is hope to benefit the society by increasing their intrest to learn deeper about mathematics. To solve this problem, the solution offered as follows: introducing one of the unique geometry of platonic solid, through everyday life objects. In this case, as the student of Mathematics Education Study Program Teaching and Science Faculty of Universitas Kristen Indonesia (UKI), is making platonic solid lantern to introduce platonic solid to the society. Platonic solid is the combination of five geometry shapes composed by tetrahedron, hexahedron, dodecahedron, octahedron, and icosahedron.Keywords: Platonic solid (tetrahedron, hexahedron, dodecahedron, octahedron, dan icosahedron).